A comunicação dos impactos socioambientais no EIA e sua retransmissão para o RIMA: um estudo comparativo das estratégias de comunicação das Hidrelétricas de Estreito e São Salvador - Magrin, Virgínia de Figueiredo (Universidade Federal do Tocantins, 2016)
This research paper aims to understand the communication process of socioenvironmental impacts in EIA as well as how this information is passed along to RIMA, through a comparative study of communication strategies from Estreito and São Salvador hydroelectric facilities. In this process, it was analyzed around 400 pages listing 146 different impacts through a content analysis. For a better understanding of the data analyzed, this research categorized the material into two ways: a qualitative study using text inferences and a quantitative study counting the impacts, citations, comparisons and/or the hydroelectric facilities of other places and the given space of them. The collected data showed that the study and the reports of each hydroelectric facility are different; the ones EIAs, even though they are distinct, they presented errors in their communication strategies; the ones RIMAS don’t accomplish the requirements in terms of resolution and constitution – the communication transparency with the local population about big projects.